2017
DOI: 10.1155/2017/8919546
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Echinococcosis: A Case of Extrahepatic Intra-Abdominal Involvement

Abstract: Hydatid disease, or echinococcal disease, is a parasitic infestation caused by the larval stage of the Echinococcus tapeworm and it primarily affects the liver and lung but involvement of other organs is also possible secondary to peritoneal seeding or hematogeneous dissemination. We describe a rare case of extensive abdominal disease, with lesions affecting the liver, peritoneum, and lesser omentum, requiring aggressive surgical intervention. Complementary diagnostic exams were crucial to reach the diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
5
0
3
Order By: Relevance
“…Los herbívoros, como huéspedes intermedios, son contaminados por la digestión de los huevos en alimentos o agua contaminados. Posteriormente, las oncósferas salen de los huevos y entran al torrente sanguíneo y llegan al hígado a través de la vena porta, afectando inicialmente el lóbulo derecho, pero pueden extenderse a todo el parénquima (7,8).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Los herbívoros, como huéspedes intermedios, son contaminados por la digestión de los huevos en alimentos o agua contaminados. Posteriormente, las oncósferas salen de los huevos y entran al torrente sanguíneo y llegan al hígado a través de la vena porta, afectando inicialmente el lóbulo derecho, pero pueden extenderse a todo el parénquima (7,8).…”
Section: Discussionunclassified
“…La sintomatología es inespecífica por compresión de órganos vecinos (vejiga o recto), infertilidad y alteraciones menstruales. En algunos casos, puede comprimir los uréteres y provocar insuficiencia renal (8). Una vez realizado el diagnóstico, es obligatorio excluir la hidatidosis pulmonar, ya que su tratamiento tiene prioridad antes de cualquier intervención quirúrgica en otra localización anatómica (2,12).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…4,5,10 Treatment of HD Small, calcified cysts do not require treatment but should be monitored. 1 Treatment options can be divided into chemotherapy (benzimidazolic drugs) and surgery, which consist of PAIR (Puncture, Aspiration, Injection, Respiration), PPDC (Percutaneous Puncture with Drainage and Curettage), conservative surgery (open cystectomy with or without omentoplasty), and radical surgery (total pericystectomy or partial hepatectomy). Palliative treatment consists of simple tube drainage of infected cysts or communicating cysts.…”
mentioning
confidence: 99%
“…In the case of alternative medical therapy using chemotherapy alone, albendazole is used with an adult dosage of 400mg orally, twice a day for 1-5 months and a pediatric dosage of 15 mg/kg/day (maximum of 800mg) for 1-6 months. 1,4,5,10,11 Study by Gourgiotis S and collegues on 169 patients of hydatid cysts in a 12 years period showed that surgical procedures combined with antiscolicidal agents like albendazole were more effective in treatment of hepatic hydatid cysts.…”
mentioning
confidence: 99%